Digital arithmetic - Ercegovac, Miloš D. (Morgan Kaufmann Series in Computer Architecture and Design., 2004)
"Digital Arithmetic" plays an important role in the design of general-purpose digital processors and of embedded systems for signal processing, graphics, and communications. In spite of a mature body of knowledge in digital arithmetic, each new generation of processors or digital systems creates new arithmetic design problems. Designers, researchers, and graduate students will find solid solutions to these problems in this comprehensive, state-of-the-art exposition of digital arithmetic. Ercegovac and Lang, two of the field's leading experts, deliver a unified treatment of digital arithmetic, tying underlying theory to design practice in a technology-independent manner. They consistently use an algorithmic approach in defining arithmetic operations, illustrate concepts with examples of designs at the logic level, and discuss cost/performance characteristics throughout. Students and practicing designers alike will find "Digital Arithmetic" a definitive reference and a consistent teaching tool for developing a deep understanding of the "arithmetic style" of algorithms and designs.; It guides readers to develop sound solutions, avoid known mistakes, and repeat successful design decisions. It presents comprehensive coverage from fundamental theories to current research trends. It is written in a clear and engaging style by two masters of the field. It concludes each chapter with in-depth discussions of the key literature. It includes a full set of over 250 exercises, an on-line appendix with solutions to one-third of the exercises and 600 lecture slides